Tetragonal structure, anionic vacancies and catalytic activity of SO42−-ZrO2 catalysts for n-butane isomerization - Vera, Carlos Roman (2002)
Abstract An assessment of the influence of the crystal structure, surface hydroxylation state and previous oxidation/reduction pretreatments on the activity of sulfate-zirconia catalysts for isomerization of n-butane was performed using crystalline and amorphous zirconia supports. Different sulfation methods were used for the preparation of bulk and supported SO42−-ZrO2 with monoclinic, tetragonal and tetragonal+monoclinic structures. Activity was important only for the samples that contained tetragonal crystals. The catalysts prepared from pure monoclinic zirconia showed negligible activity. SO42−-ZrO2 catalysts prepared by sulfation of crystalline zirconia displayed sites with lower acidity and cracking activity than those sulfated in the amorphous state. Prereduction of the zirconia samples with H2 was found to greatly increase the catalytic activity, and a maximum rate was found at a reduction temperature of 550–600 °C, coinciding with a TPR peak supposedly associated with the removal of lattice oxygen and the creation of lattice defects. A weaker dependence of catalytic activity on the density or type of surface OH groups on zirconia (before sulfation) was found in this work. A model of active site generation was constructed in order to stress the dependence on the crystal structure and crystal defects. Current and previous results suggest that tetragonal structure in active SO42−-ZrO2 is a consequence of the stabilization of anionic vacancies in zirconia. Anionic vacancies are in turn supposed to be related to the catalytic activity for n-butane isomerization through the stabilization of electrons from ionized intermediates.